The creation :an appeal to save life on earth /(Acc: D 194) an appeal to save life on earth - Wilson, Edward O. (New York : Norton, 2006)
" Like Rachel Carson's Silent Spring, this is a book about the fate of the earth and the survival of our planet. Wilson attempts to bridge the seemingly irreconcilable worlds of fundamentalism and science. Passionately concerned about the state of the world, he draws on his own personal experiences and expertise as an entomologist, and prophesies that half the species of plants and animals on Earth could either have gone or at least are fated for early extinction by the end of our present century. This is not a bitter, predictable rant against fundamentalist Christians or deniers of Darwin; rather, Wilson, a leading "secular humanist," draws upon his own rich background as a boy in Alabama who "took the waters," and seeks not to condemn this new generation of Christians but to address them on their own terms.--From publisher description.
Keywords: Biology; Creation